Dynamic Changes of Active Components in Greengage (Prunus mume) Wine During Fermentation - Wang, Yan; Zhang, Yuxin; Cao, Pengliang; Chen, Pengfei; Chen, Xianggui; Tandhanskul, Atittaya (Applied Science and Engineering Progress, 2025)
Greengage wine is abundant in functional active ingredients, such as phenolics, which interact with proteins to induce turbidity. Therefore, understanding the dynamic changes during fermentation is essential for controlling the quality of greengage wine. In this study, the production process of four different greengage wines was designed by cross-fermentation of two yeasts and two enzyme preparations. The results indicated that variations in alcohol content, reducing sugars, pH, and soluble solids were primarily associated with the selected fermentation microorganisms. However, no significant differences were observed among the four processes. Notably, protein content varied significantly, reaching up to 142.82 ± 20.90 mg·L⁻1. The total phenol content exhibited a downward trend and ultimately stabilized at approximately 388.92 ± 2.39 mg/L. Conversely, total flavonoid content initially increased before experiencing a slight decline, thus indicating that the fermentation process had a substantial impact on its levels. Tannin content remained relatively stable throughout fermentation. Analysis of monomeric phenols revealed that greengage wine contained 14 common monomeric phenols, with chlorogenic acid being present at the highest concentration. Antioxidant activity in greengage wine continued to rise during the early stage of fermentation, peaking on day six before subsequently declining thereafter. These findings provide valuable insights for the further development of greengage wine.